Wednesday

April 16, 2014

April 16, 2014

Posted by **Raven** on Thursday, October 18, 2012 at 9:00am.

- Math -
**Reiny**, Thursday, October 18, 2012 at 9:28amsince we know 3 is a roots, x-3 must be a factor, so

2x^3 - 11x^2 + 12x + 9

= (x-3)(2x^2 - 5x - 3)

= (x-3)(x-3)(2x+1)

so .....

**Related Questions**

Math--help help help - 1)when a certain polynomial is divided by x - 3, the ...

Math-helpppppp - 1)when a certain polynomial is divided by x - 3, the quotient ...

math - I solved this problem 12x-6=11x -6+6=0 11x+6 12x=11x+6 12x-11x=x 11x-11x=...

math - what is the equation of a line that passes through (1,-4) and (2,7)? a. y...

algebra - 1)Solve by factoring:5x^2=4-19x answer=-4,1/5 2)Which quadratic ...

ALGEBRA -- long division - Find each solution using long division. Show your ...

Math-Quartic Equation - Reduce this equation using the quadratic formula, ...

Add the Polynomials - (9X^3+2X^2-7)+(2X^3-2X+9) IS ANSWER: 11X^3+2X^2-2X+2

Algebra - 1)Solve by factoring:5x^2=4-19x answer=-4,1/5 2)Which quadratic ...

need help - Factor Completely (x-4(x^2+3) Perform the indicated operations (-(...